2018
DOI: 10.1186/s12858-018-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a detection assay for DNA endonuclease activity and its application in the screening and prognosis of malignant lymphoma

Abstract: BackgroundEndonucleases play critical roles in maintaining genomic stability and regulating cell growth. The purpose of this study was to evaluate detection of endonuclease activity as an indicator in the early diagnosis and prognosis of lymphoma.ResultsThe method of endonuclease activity determination was successfully established and applied to compare cancer patient and control cohorts. Endonuclease activities of cancer tissues were significantly higher than those of adjacent control tissues (P < 0.001). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…But after UV treatment, the results were dramatically changed, the percentage of G0/G1 in MUS-KD cells was significantly decreased, and cell cycle progression was arrested at S phase (Figure 2CII). In our related study, we also found that the total endonuclease activity of MUS-KD cells was decreased due to the arrest of DNA synthesis in mitosis after MUS81 silencing (18).…”
Section: Resultsmentioning
confidence: 78%
“…But after UV treatment, the results were dramatically changed, the percentage of G0/G1 in MUS-KD cells was significantly decreased, and cell cycle progression was arrested at S phase (Figure 2CII). In our related study, we also found that the total endonuclease activity of MUS-KD cells was decreased due to the arrest of DNA synthesis in mitosis after MUS81 silencing (18).…”
Section: Resultsmentioning
confidence: 78%